Implementasi Voice Detection dan Geolocation Aplikasi Pelaporan Kejahatan di Jalan Raya Realtime Berbasis Mobile - Restu Sofyan Ma'arif; Rodhiyah Mardhiyyah (Journal of Information System Research (JOSH), 2025)
The prevalence of public space crimes, particularly street crimes like mugging and klithih, has become a crucial issue disrupting community safety and comfort. Current emergency reporting systems, which rely on phone calls or direct visits to police stations, are often hampered by time delays, reducing the effectiveness of intervention. To address this, an integrated crime reporting system is proposed through an Android mobile application developed using the Waterfall method. This solution enhances conventional systems by implementing Geolocation and Voice Detection technologies. Geolocation enables precise mapping of incident locations, ensuring location data remains accurate to within 9 meters even with a weak GPS signal Meanwhile, Voice Detection acts as the initial trigger for crime reporting. It proactively analyzes ambient audio for specific shout patterns, which indicate an emergency. The model achieves an accuracy of 0.9590% in noisy environments. Upon detection, the system automatically sends simultaneous emergency notifications to all nearby app users and security authorities within 2 seconds. This application is expected to significantly optimize crime response times, contributing tangibly to enhancing public safety and security.